(3GdSjQI GdfHhjIs - (3GHf gTGe, YHO Gdedc Hf gTGe Hf CjhH,s (3J(B. 213 (3g`(B.s; (3bWH, eMeO Ydj,s 1346 (3g`(B-s ((3HjQhJ (B:s (3GdecJHI GdYUQjI,s, 2005)
(3jJfGhd GdcJGH SjQI QShd Gddg Udi Gddg Ydjg hSde ef bHd hdGOI GdQShd Udi Gddg Ydjg hSde hPcQ SQO GdfSH Edi SjOfG BOe Ydjg GdSdGe hHYO GdhdGOI hfTCJg bHd GdOYhI hHYO hGfJTGQgG hGdZRhGJ hGdaJhMGJ MJi haGJg Udi Gddg Ydjg hSde(B.s
Keywords: (3eMeO (B((3Udi Gddg Ydjg hSde(B)(3,s -- 53 (3b(B. (3g`(B-11 (3g`(B.s; (3GdSjQI GdfHhjIs